RETRACTION: [EFFECTS OF SCIENTIFIC INQUIRY LEARNING MODEL AND LOGICAL THINKING ABILITY OF SENIOR HIGH SCHOOL STUDENTS SCIENCE PROCESS SKILLS] - M.Akhyar Lubis; Mara Bangun Harahap; Sondang R Manurung (Jurnal Pendidikan Fisika, 2017)
This article was withdrawn based on a request from the author (MAL) and consideration of the JPF editorial team that there had been a double submission.